2021
DOI: 10.1073/pnas.2025658118
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of Mycobacterium smegmatis DyP-loaded encapsulin

Abstract: Encapsulins containing dye-decolorizing peroxidase (DyP)-type peroxidases are ubiquitous among prokaryotes, protecting cells against oxidative stress. However, little is known about how they interact and function. Here, we have isolated a native cargo-packaging encapsulin from Mycobacterium smegmatis and determined its complete high-resolution structure by cryogenic electron microscopy (cryo-EM). This encapsulin comprises an icosahedral shell and a dodecameric DyP cargo. The dodecameric DyP consists of two hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…DypB (class P) from R. jostii was shown to assemble with encapsulin in vitro [ 12 ], suggesting the potential of class P DyPs to act as cargo proteins of encapsulin. A recent high-resolution cryogenic electron microscopy study revealed that a DyP-type peroxidase from Mycobacterium smegmatis is a primary cargo protein of mycobacterial encapsulins [ 89 ]. Notably, this latter study noted that the encapsulin shell plays a role in stabilizing DyP in a dodecameric form, which is larger than any previously reported DyP oligomer.…”
Section: Physiological Role Of Dyp-type Peroxidasesmentioning
confidence: 99%
“…DypB (class P) from R. jostii was shown to assemble with encapsulin in vitro [ 12 ], suggesting the potential of class P DyPs to act as cargo proteins of encapsulin. A recent high-resolution cryogenic electron microscopy study revealed that a DyP-type peroxidase from Mycobacterium smegmatis is a primary cargo protein of mycobacterial encapsulins [ 89 ]. Notably, this latter study noted that the encapsulin shell plays a role in stabilizing DyP in a dodecameric form, which is larger than any previously reported DyP oligomer.…”
Section: Physiological Role Of Dyp-type Peroxidasesmentioning
confidence: 99%
“…Based on our finding, we speculate that the 3fold symmetry of the dye-decolorizing peroxidase (DyP) cargo mentioned briefly in the introduction and found in related encapsulins should bind the 3-fold axis of the shell. However, a concurrent structural study of the M. smegmatis DyP encapsulin appears to have the most defined cargo density positioned proximal to the 5-fold axis of the shell rather than the 3-fold axis (15). Without an abundance of structural data on diverse encapsulins, it remains unclear what role symmetry plays in the cargo-shell interaction.…”
Section: The Flp Cargo Protein Is Flexibly Bound Within the Encapsulin Shellmentioning
confidence: 99%
“…For the B. linens DyP encapsulin, only a single cargo protein was encapsulated despite additional space within the shell (13,14). However, a recent study of the M. smegmatis DyP encapsulin found both a minority species of the encapsulin contained a single hexameric DyP cargo while the majority of particles actually contained a dodecameric DyP complex from 2 DyP cargo interacting with one another (15). Furthermore, encapsulation of native and non-native cargo appears to cause significant destabilization of the nanocompartment (13,14), which may explain the absence of higher cargo loading ratios in many of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…At present, eight encapsulins have been resolved at near-atomic resolution by X-ray crystallography or three-dimensional cryo-electron microscopy (3D cryo-EM). These are the encapsulins from the archaeon P. furiosus (EncPf; PDB entry 2e0z) [29], and from the bacteria T. maritima (EncTm; PDB entry 3dkt) [6], Myxococcus xanthus (EncMx; PDB entry 4pt2) [30], Quasibacil-lus thermotolerans (EncQt; PDB entry 6nj8) [49], Synechococcus elongatus (EncSe; PDB entry 6 × 8 m) [31], Mycolicibacterium hassiacum (EncMh; PDB entry 6i9g) [50], Mycobacterium smegmatis (EncMs; PDB entry 7boj) [51], and Haliangium ochraceum (EncHo) [52]. All these encapsulins except EncSe are close relatives and are grouped in the classical family 1; EncSe belongs to family 2A and has distinctive structural and functional features.…”
Section: Nanocompartment Structurementioning
confidence: 99%
“…The TP-mediated, flexible interactions between the cargo and the encapsulin shell contribute to the low resolution observed for the encapsulated cargo. In the EncMs system, however, the dye-decolorizing peroxidase (DyP) cargo was clearly resolved in the cryo-EM structure [51]. DyP forms a dodecameric complex of two hexamers that stretches across the interior of the encapsulin, which contributes to DyP stability.…”
Section: Nanocompartment Structurementioning
confidence: 99%